(3GdeHOC hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfi CQjO Cf COd ai gPg GdebGdg Ydi Mbjbg eG YfO GdeTGFjf GdeMUdjf GdebGdI GdChdi ai EKHGJ GdeHOC GdChd ddcd hhMOGfjJg hJYOjO GdUaGJ GdJi jdjb Hg s
(3BNQgG (B:s
(3hEf cGfJ ef GdbhI HMjK GdChdi Cf fPcQ hdcf jDKQ GdEjVGM hGdGNJUGQ JeJ eSCdI GdeHOC hGdeYGO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1456s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs